Norway spruce (Picea abies (L.) Karst.) damage in the Zasavje district of Slovenia evaluated by two methods - Vidergar-Gorjup, Natalija (Zbornik gozdarstva in lesarstva, 2000)
The Zasavje district has been heavily affected by air pollution due to mining,the presence of a coal-fired power plant, and industry. The extent of forest damage differs according to location because of specific climatic and orographic characteristics. Norway spruce damage was estimated by two methods at 10 locations in the Zasavje district using the Slovenian forestry method for the estimation of forest damage (KOVA et al. 1995), and a Czech method forestimation of damage to the branching system and needle loss and discoloration (CUDLIN & CHMELIKOVA 1995). Comparison of the results obtained by the two methods gave similar damage assessments at heavily polluted sites, although the data obtained by the two methods differ due to several environmental parameters. The Czech method did not give as good results as wasexpected. A possible reason might be that spruce trees in the investigated locations are less damaged than those in the Czech Republic, where the method was developed.
Keywords: Central Sava Valley; propadanje gozdov; smreka; Zasavje